Cryptocoryne ×batangkayanensis (Araceae), a new hybrid from Sarawak - Isa, Ipor; Marian, Orgaard; Niels, Jacobsen (BGBM Berlin-Dahlem., 2015)
A new hybrid species, Cryptocoryne ×batangkayanensis Ipor, Ørgaard & N. Jacobsen (C. cordata var. grabowskii (Engl.) N. Jacobsen × C. ferruginea Engl. var. ferruginea), from the Batang Kayan basin, Sarawak, Malaysia, is described and illustrated. It is compared with the parent species and an artificial hybrid of the same parentage.